(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
This article provides a scientific analysis of the aesthetic, ecological, and functional significance of landscaping on the campuses of higher education institutions (HEIs) in Osh. Universities occupy a special place in the urban landscaping system and are considered an important city-forming factor. The main objective of this study is to develop a scientifically based methodology for landscaping university campuses, taking into account the negative impact of the urban environment (gas, dust, noise), and recommending an optimal selection of permanent plantings. The study included the campuses of four major universities in Osh (OshMU, OshTU, OshMPU, and KOEAU). The landscape assessment was based on determining the percentage of greenery, plant condition, sanitary, hygienic, and aesthetic indicators. The main results of the study: the condition of the plants is generally satisfactory, but in some areas dead trees need to be replaced; the highest aesthetic and sanitary-hygienic indicators were recorded on the grounds of universities in the southeastern part of the city; the need to strengthen the protective function of the landscaping of educational institutions located near highways from urban dust and gases was noted. The following recommendations were made: increasing the number of species of resistant, ornamental, and environmentally friendly plants (e.g., prickly spruce, hawthorn, white poplar, berry bush); dividing the university territory into functional zones (educational and practical, park, residential, sports, economic); organizing architectural objects and green spaces into a single ensemble, creating aesthetically and environmentally favorable conditions for students. Scientific novelty of the study: For the first time, the principles of landscaping and landscape organization of university grounds in the city of Osh have been comprehensively studied and practical recommendations have been developed